Leibniz : the nature of reality and the reality of nature : a study of Leibniz's double-aspect ontology and the labyrinth of the continuum /: the nature of reality and the reality of nature : a study of Leibniz's double-aspect ontology and the labyrinth of the continuum. (2010) - Unknown
No abstract available